Peranan Lembaga Bantuan Hukum Dalam Penanganan Anak Dibawah Umur Yang Berhadapan Dengan Hukum (Studi Kasus Tahun 2018-2023 Di Kota Padang) - Rahmad Perganda; Engrina Fauzi (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Childreniasiperpetratorsioficriminaliactsialsoineed to receive serious attention from various related parties, because children who commit criminal acts also have theirightitoiprotection fromialliformsiof discrimination inilaw, the right to guarantees prohibiting child torture and inhumane punishment, the right to Procedural Law. Juvenile Justice, theirightitoiobtainilegal aidibothiinsideiandioutsideitheiCourt and so on. Juvenile courts require defendants to be accompanied by legal counsel, parents, guardians or foster parents, and community counselors. They have their own roles, legal advisors/advocates have a different position from parents, guardians or community counselors. (1) Whatiisitheiroleiof the Legal Aid Institute inihandling casesiofiChildreniiniConflictiwithitheiLaw (ABH) in Padang City. (2) How effective is theiroleiofiLegaliAidiInstitutionsiinihandlingicasesiofiChildreniiniConflictiwithitheiLaw (ABH) in Padang City. Theirole of Legal Aid Institutions in Handling Children in Conflictiwith theiLaw, includes accompanying ABH at every level of examination so thatiABH's rightsiare guaranteed both before, during and after the trial and seeking diversion in children's cases so that children are not directly affected by crime or punishment. Data from year 2020 to 2023 showsithatitheirole of Legal Aid Institutions in handlingichildreniin conflictiwith theilaw has notibeenieffective,ibutitheihandlingiisiiniaccordanceiwithiLawiNumberi11iofi2012 concerningitheiJuvenileiCriminaliJusticeiSystemiand procedures in LawiNumber 16 of 2011 concerningiLegal Aid . The obstacles faced that make it ineffective areithe lackiofiperspective ofilawienforcementiofficialsiregardingichildren and the lack of understanding of law enforcement officials regarding theiJuvenileiCriminaliJusticeiSystemiAct, so this makes it very difficult for the process of assisting children by Legal Aid Institutions.